2017
DOI: 10.1111/spc3.12293
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of agency: Belief in free will as a unique and important construct

Abstract: Belief in free will is the general belief that human behavior is free from internal and external constraints across situations for both self and others. In the last decade, scholars in social-cognitive psychology and experimental philosophy have made progress in defining free will terms, exploring how laypersons think of free will, discovering related cognitive processes and biases, and examining the behavioral outcomes of believing in free will. The growing interest in this construct raises the need for a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 106 publications
1
47
0
Order By: Relevance
“…This seems especially important, given that questions on the issue of free will and determinism immediately also raise questions about moral responsibilityÑand hence praise, blame, and criminal accountability (see Greene & Cohen, 2004, for a review). In fact, psychological research on lay theories about free will and determinism found that these beliefs indeed crucially affect peopleÕs cognitions and behaviors in various domains, and that they are important constructs that capture unique aspects of agency (Feldman, 2017).…”
Section: Psychological Research Into Lay Peopleõs Belief In Free Willmentioning
confidence: 99%
“…This seems especially important, given that questions on the issue of free will and determinism immediately also raise questions about moral responsibilityÑand hence praise, blame, and criminal accountability (see Greene & Cohen, 2004, for a review). In fact, psychological research on lay theories about free will and determinism found that these beliefs indeed crucially affect peopleÕs cognitions and behaviors in various domains, and that they are important constructs that capture unique aspects of agency (Feldman, 2017).…”
Section: Psychological Research Into Lay Peopleõs Belief In Free Willmentioning
confidence: 99%
“…For example, a person may perceive that everything in life is causally determined by the laws of nature or that all actions are predestined by the rule of God or fate, with no capacity for humans to effectively choose their own course of action. Importantly, in both the academic conceptualization and in laypersons’ understanding of the concept of free will, free will is not about metaphysics and is not a mysterious dualistic force, but rather it is a concept representing the capacity for choice and agency ( Baumeister, 2008 ; Feldman, 2017 ; Monroe, Dillon, & Malle, 2014 ; Monroe & Malle, 2014 ; Nadelhoffer, Shepard, Nahmias, Sripada, & Ross, 2014 ; Nahmias, Shepard, & Reuter, 2014 ).…”
Section: Belief In Free Willmentioning
confidence: 99%
“… Feldman (2017) provided an in-depth review highlighting belief in free will as a unique and important agency construct, discussing conceptual differences from other well-known agency constructs in the literature and the related empirical evidence.…”
Section: Belief In Free Willmentioning
confidence: 99%
“…43 Self-efficacy on the other hand, has been described as a core judgment or evaluation of one's ability to perform and succeed at tasks. 44,45,46 Researchers argue that self-efficacy is different from free will in that self-efficacy is concerned with one's personal evaluation of efficacy, whereas free will captures aspects of choice and agency. 47 The differences between the two constructs have been described as being centered on the fact that "one can perceive the self as incapable and still believe that self is free to choose whether to undertake the action or not."…”
Section: Challenge 1: Definition(s)mentioning
confidence: 99%